Sacral Peak Pressure in Healthy Volunteers and Patients With Spinal Cord Injury: With and Without Liquid-Based Pad. Issue 4 (July 2015) - Duetzmann, Stephan; Forsey, Lynn M.; Senft, Christian; Seifert, Volker; Ratliff, John; Park, Jon
Abstract : Background: The prevalence of sacral pressure ulcers in patients with spinal cord injuries is high. The sacral area is vulnerable to compressive pressure because of immobility and because the sacrum and posterior superior iliac prominence lie closely under the skin with no muscle layer in between. Objective: The aim of this study was to assess peak sacral pressure before and after use of PURAP, a liquid-based pad that covers only the sacral area and can be applied on any bed surface. Methods: Healthy volunteers ( n = 12) and patients with spinal cord injuries ( n = 10) took part; the patients had undergone spine surgery within 7 days before data collection. Participants were in bed, pretest pressure maps were generated, PURAP was placed for 15 minutes, and then posttest pressure maps were generated. Peak pressure was obtained every second and averaged over the entire period. Patients rated whether their comfort had improved when PURAP was in use. Results: For healthy volunteers, mean pretest peak sacral pressure was 74.7 ( SD = 16.2) mmHg; the posttest mean was 49.1 ( SD = 7.5) mmHg ( p < .001, Wilcoxon signed-rank test). For patients with spinal cord injuries, mean pretest peak sacral pressure was 105.7 ( SD = 22.4) mmHg; the posttest mean was 81.4 ( SD = 18.3) mmHg ( p < .001, Wilcoxon signed-rank test). The pad reduced the peak sacral pressure in the patient group by 23% (range = 11%–42%) and in the volunteers by 32% (range = 19%–46%). Overall, 70% of the patients reported increased comfort with PURAP. Discussion: Peak sacral pressure was reduced when PURAP was used. It covers only the sacral area but could help many patients with spinal cord injury because the prevalence of sacral pressure ulcers is high in this group. PURAP may be economically advantageous in countries and hospitals with limited financial resources needed for more expensive mattresses and cushions.